Perancangan Strategic Dashboard Pemetaan Alumni Menggunakan Metode PureShare - Dicki Fathurohman; Rani Megasari; Muhammad Nursalman (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
Alumni play a crucial role as university representatives in society and as a bridge connecting networks and sharing information with current students and new graduates. However, limited up-to-date alumni data and low participation in data updates hinder universities from fully leveraging alumni potential. This study aims to develop a strategic alumni mapping dashboard for Universitas Pendidikan Indonesia (UPI) using the PureShare method, which emphasizes alignment between organizational goals and user needs. The development process includes planning and design, system and data review, prototype creation, refinement, and release. During planning, objectives and key results were identified as the foundation for dashboard design. The data review stage revealed several missing key data, such as income, employment status, and further study data, which were subsequently added to complete the database. The prototype was tested through blackbox testing and refined based on user feedback. The final dashboard presents interactive visualizations, including alumni growth trends, distributions by domicile, employment, entrepreneurship, and further study. This dashboard serves as a monitoring and strategic decision-making tool for UPI’s Alumni Association, supporting the achievement of university Key Performance Indicators, particularly graduate success. This research highlights the importance of participatory approaches and user-centered design in enhancing the effectiveness of alumni mapping dashboards.